EVALUATING THE INTERACTION BETWEEN PLATYCERATID GASTROPODS AND CRINOIDS: A COST-BENEFIT APPROACH - Baumiller T.K. (My University, 2003)
The association of platyceratid gastropods and crinoids is preserved in the fossil record of the Ordovician through the Permian. The association has been generally interpreted as involving coprophagy, although recent suggestions of gametophagy and kleptoparasitism are supported by new data. Whether platyceratids were coprophagous, gametophagous, or kleptoparasitic, they would have had to obtain their energy from the crinoid without killing it. Under that scenario, the sum of nutrients captured by the crinoid would have had to support the host and the infestor. This is explored quantitatively using a cost-benefit analysis. The results suggest that (1) some crinoids were well capable of capturing sufficient nutrients to fulfill their metabolic needs as well as those of the infesting platyceratids, (2) the preference of platyceratids to infest pinnulate crinoids rather than non-pinnulate crinoids is consistent with the cost-benefit analysis, (3) under most circumstances, a parasitic strategy of platyceratids would have provided them with a greater energetic return than would a predatory strategy.
Keywords: PALEOZOIC; PARASITISM; PREDATION; MODELING; Paleozoic; Палеозой